American Power and Security during the Bosnian War (1993–1995): National Identity, Credibility, and the 'Stalemate Machine'. Issue 4 (4th July 2017) - Keller, Jonathan W.; Kaussler, Bernd; Yang, Yi Edward
Abstract: This manuscript uses recently declassified documents to examine the factors shaping US policy toward Bosnia from 1993 to 1995. Drawing upon IR theoretical insights from constructivism and realism, these documents reveal that the halting and inconsistent nature of US actions during this period can be explained by a mismatch between US identity-driven goals and the constraints of the post-Cold War world. Having committed themselves to bold yet largely unattainable objectives in the region, US officials feared a loss of credibility and, for much of the period under investigation, did just enough not to 'lose' Bosnia without taking the kinds of decisive actions that would have made a difference on the ground. Eventually, atrocities in Sarajevo and Srebrenica convinced the US that more forceful action was necessary to preserve US and NATO credibility.